2000
DOI: 10.1034/j.1399-3089.2000.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐depleting anti‐CD4, but not anti‐CD8, antibody induces long‐term survival of xenogeneic and allogeneic hearts in α1,3‐galactosyltransferase knockout
(GT‐Ko) mice

Abstract: The anti-galactose-alpha1,3-galactose (Gal) antibody (Ab) response following pig-to-human transplantation is vigorous and largely resistant to currently available immunosuppression. The recent generation of GT-Ko mice provides a unique opportunity to study the immunological basis of xenograft-elicited anti-Gal Ab response in vivo, and to test the efficacy of various strategies at controlling this Ab response [1]. In this study, we compared the ability of non-depleting anti-CD4 and anti-CD8 to control rejection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…Heterotopic rat hearts were transplanted into the abdomen of the recipient by anastomosing the donor aorta to recipient aorta and the donor pulmonary artery to recipient inferior vena cava as previously described (33). Anti-Gal mAb were administered by i.v.…”
Section: Galmentioning
confidence: 99%
“…Heterotopic rat hearts were transplanted into the abdomen of the recipient by anastomosing the donor aorta to recipient aorta and the donor pulmonary artery to recipient inferior vena cava as previously described (33). Anti-Gal mAb were administered by i.v.…”
Section: Galmentioning
confidence: 99%
“…The kinetics were delayed and the titers of the antigraft IgG response was significantly reduced in C57BL/6 compared with BALB/c recipients. We have previously reported that the mouse antirat IgM response is T-cell dependent and is inhibited by nondepleting anti-CD4 mAbs or costimulation blockade with CTLA4-Ig and anti-154 (22,25). However neither the rate nor magnitude of the antigraft IgM response was affected by the absence of IFN-g or IL-4.…”
Section: Discussionmentioning
confidence: 95%
“…Lewis rats were purchased from Harlan (Walkersville, MD). Mice received heterotopic cardiac transplants from allo (BALB/c) or xeno (Lewis) donors, as previously described (21,22). The heart grafts were monitored daily until rejection, and rejection was defined as complete cessation of pulsation.…”
Section: Mice and Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ␣1,3-galactosyltransferase (Gal Ϫ/Ϫ ) knockout mouse, which lacks the expression of the Gal epitope, has been used as a recipient for studying anti-Gal responses to Gal ϩ/ϩ cardiac xenografts (12)(13)(14)(15)(16). Preformed anti-Gal Abs are primarily IgM, whereas the elicited anti-Gal IgG Abs following xenotransplantation of Lewis rat hearts were restricted to the IgG3 and IgG1 subclasses (14).…”
mentioning
confidence: 99%